(untitled) (CIPEEX, 2022)
THERAPEUTIC HYPOTHERMIA IS USED AS A TREATMENT WITH THE INTENTION OF REDUCING MORTALITY AND NEUROLOGICAL SEQUELAE IN NEONATES WITH RESPIRATORY HYPOXEMIC DAMAGE. THUS, THIS STUDY SOUGHT TO DESCRIBE THE BENEFITS AND HARMS FOR NEWBORNS ADMITTED TO THIS TREATMENT OBJECTIVE: TO IDENTIFY THE BENEFITS AND HARMS OF THERAPEUTIC HYPOTHERMIA IN NEWBORNS WITH HYPOXIC-ISCHEMIC ENCEPHALOPATHY. METHODOLOGY: THIS IS AN INTEGRATIVE LITERATURE REVIEW, CARRIED OUT IN PUBLISHER MEDLINE, SCIENCE DIRECT, SCIENTIFIC ELECTRONIC LIBRARY ONLINE AND GOOGLE SCHOLAR DATABASES, PUBLISHED FROM 2017 TO 2022, IN PORTUGUESE, ENGLISH AND SPANISH AND IN OPEN ACCESS . RESULTS: 15 ARTICLES WERE SELECTED, APPROVED FOR ANALYSIS AND READING IN FULL. BENEFICIAL ASPECTS WERE EVIDENCED FROM THESE STUDIES, AMONG THEM, THE REDUCTION OF MORTALITY, THE SEVERITY OF RESPIRATORY DAMAGE, NEURAL AND GASTROINTESTINAL DAMAGE, AND THE IMPROVEMENT OF OXIDATIVE FUNCTIONS. ON THE OTHER HAND, HARMFUL FACTORS SUCH AS COMPLICATIONS DURING THERAPY, DEVELOPMENTAL DELAY AND BRADYCARDIA WERE FOUND. CONCLUSION: THIS REVIEW SHOWED BENEFITS AND HARMS RELATED TO THE USE OF THERAPEUTIC HYPOTHERMIA IN NEONATES. HOWEVER, IT DEMONSTRATES THE NEED FOR MORE CONSISTENT STUDIES TO APPLY THE TECHNIQUE AND ITS CONSEQUENCES, AS WELL AS TO IMPROVE THE PROCEDURE AND ITS USE, TO GUARANTEE THE QUALITY OF LIFE OF NEONATES WITH HYPOXIC-ISCHEMIC ENCEPHALOPATHY.